Artificial Intelligence and Crisis Communication: A Qualitative Analysis within the Framework of the Technology Acceptance Model (TAM) in Public Relations. - Sandıkcı, Yılmaz Türker; Soy, Samed (Electronic Turkish Studies)
In the era of digital transformation, crisis communication practices are being redefined, while artificial intelligence (AI) technologies have emerged as a strategic tool in the field of public relations. Although scholarly interest in the integration of AI into communication processes has increased, limited research has examined how public relations professionals perceive and adopt these technologies in their professional practice. This study explores the dynamics of AI technology acceptance within the context of crisis communication in public relations. The primary aim is to analyze public relations professionals’ perceptions, attitudes, and intentions toward the use of AI-based applications. Drawing on the Technology Acceptance Model (TAM), the research provides a theoretical framework for understanding individuals’ acceptance processes regarding AI technologies. Employing a qualitative research design, semi-structured interviews were conducted with 14 public relations specialists working in public and private sectors in Istanbul. Data were analyzed through a content analysis and evaluated based on TAM variables—perceived usefulness, perceived ease of use, attitude, intention to use, and actual use. Findings reveal that AI tools play a strategic role across crisis phases: early warning and risk detection before crises, rapid information management during crises, and reputation restoration afterward. Participants viewed AI as a decision-support mechanism but noted ethical uncertainties, emotional limitations, and lack of human intuition as key constraints. The study contributes to the digital crisis communication literature by providing an integrative understanding of individual, organizational, and ethical factors influencing AI adoption in public relations practice.